Alumina sol / carbon nanotube composite flame-retardant polyimide foam sound absorption material and preparation method thereof

By introducing modified aluminum sol/carbon nanotubes into polyimide foam, the problems of insufficient flame retardancy and low sound absorption effect of the material are solved, and efficient flame retardant and sound absorption performance are achieved, which is suitable for a variety of complex environments.

CN119661893AActive Publication Date: 2025-03-21SOUTH CHINA UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411695655.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-03-21
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

In actual applications, existing polyimide foam materials have problems such as insufficient flame retardancy and low sound absorption effect, which is difficult to meet the needs of use in special environments.

Method used

By using aluminum sol for modified carbon nanotubes and using solution mixing method to uniformly fill it inside the polyimide foam to form a composite material, improving its flame retardant and sound absorption properties.

Benefits of technology

It significantly improves the flame retardant performance and sound absorption effect of the material, maintains the lightweight and excellent thermal insulation performance of polyimide foam, and is suitable for the interior and exterior walls of buildings, transportation facilities and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119661893A_ABST
    Figure CN119661893A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound absorption material and a preparation method thereof. The preparation method comprises the following steps: stirring and mixing aromatic dianhydride, a polar solvent I and small molecular alcohol, and carrying out reflux reaction to obtain a precursor solution; dispersing carbon nanotubes in a polar solvent II, performing ultrasonic dispersion, then adding aluminum sol, and continuing ultrasonic mixing to obtain an aluminum sol / carbon nanotube solution; stirring and mixing a flame retardant, a catalyst, a foam stabilizer and a foaming agent to obtain a compound additive; and mixing polyisocyanate, the precursor solution, the alumina sol / carbon nanotube solution and the compound additive, foaming, and curing at high temperature to obtain the alumina sol / carbon nanotube composite flame-retardant polyimide foam sound absorption material. The polyimide foam sound-absorbing material of the dispersed aluminum sol / carbon nano tube has excellent sound-absorbing and flame-retardant properties, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building material sound absorption, and in particular to an aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound absorption material and a preparation method thereof. Background Art

[0002] With the development of modern society, noise pollution has become increasingly serious, negatively impacting people's living and working environment. In order to improve this problem, the development and application of sound-absorbing materials has gradually become a research focus. In the early days, traditional sound-absorbing materials such as rock wool and glass wool were widely used due to their good sound absorption properties. However, these materials often have problems such as high density, heavy weight, and difficulty in processing, which limits their flexibility in practical applications. In recent years, with the development of materials science, polyimide foam has attracted widespread attention as a new type of sound-absorbing material due to its excellent properties such as light weight, high temperature resistance, and structural stability. However, polyimide foam also has certain limitations in practical applications, such as insufficient flame retardancy and low sound absorption effect, which makes it difficult to meet the use requirements in some special environments.

[0003] Therefore, developing a sound-absorbing material with simple preparation process, flame retardancy and excellent sound absorption performance has important practical application value and research significance. Summary of the Invention

[0004] In view of the shortcomings of the prior art, the present invention aims to provide an aluminum sol / carbon nanotube flame-retardant polyimide foam sound-absorbing material and a preparation method thereof.

[0005] Since their discovery, carbon nanotubes, a novel nanomaterial with excellent electrical conductivity, thermal conductivity, and mechanical strength, have rapidly become a key component of various high-performance composite materials. Research has shown that incorporating carbon nanotubes into polyimide foam significantly improves not only the material's mechanical and thermal properties but also its flame retardancy and sound absorption. This opens a new avenue for developing lightweight, flame-retardant, sound-absorbing materials.

[0006] Alumina sol is a colloid containing aluminum particles with excellent dispersibility and adhesion. It is commonly used to improve the flame retardancy and mechanical properties of materials. The aluminum particles in alumina sol can form aluminum oxide at high temperatures, which is very effective in improving the thermal stability and flame retardancy of composite materials. When alumina sol is combined with carbon nanotubes, the synergistic effect of the two may further enhance the overall performance of the composite material. The presence of aluminum particles can improve the dispersion of carbon nanotubes in the polyimide matrix. At the same time, by forming a dense carbonized layer, it enhances the material's fire resistance and thermal stability, thereby providing more reliable sound absorption and flame retardancy in practical applications.

[0007] The present invention uses aluminum sol to modify carbon nanotubes and uniformly fills them into polyimide foam using a solution mixing method to form a composite material. This composite material not only maintains the lightweight and excellent thermal insulation properties of polyimide foam, but also significantly improves sound absorption and flame retardancy. The carbon nanotubes filled with aluminum sol are modified to enhance their surface functional groups and improve their compatibility with the polyimide matrix. At the same time, the introduction of aluminum sol promotes the formation of a dense aluminum oxide layer in the composite material at high temperatures, effectively delaying the thermal decomposition process of the material and significantly improving its flame retardancy. The synergistic effect of the modified carbon nanotubes and aluminum sol not only enhances the air flow resistance of the material and improves its pore structure, but also improves its sound absorption efficiency. This material is particularly suitable for sound absorption and fire prevention applications in the fields of interior and exterior walls of buildings, transportation facilities, etc. It has the advantages of being green and environmentally friendly, economical and practical, and easy to construct. It can be used on a large scale in complex environments to effectively reduce noise pollution and enhance safety.

[0008] The purpose of the present invention is achieved by at least one of the following technical solutions.

[0009] A method for preparing an aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material comprises the following steps:

[0010] (1) Preparation of precursor solution: Aromatic dianhydride, polar solvent I, and small molecule alcohol are stirred and mixed, and refluxed to obtain a precursor solution;

[0011] (2) Preparation of aluminum sol-modified carbon nanotubes: The carbon nanotubes are dispersed in a polar solvent II, ultrasonically dispersed, and then aluminum sol is added and ultrasonically mixed (so that the aluminum sol is uniformly attached to the surface of the carbon nanotubes) to obtain an aluminum sol / carbon nanotube solution;

[0012] (3) Preparation of compound additives: mixing the flame retardant, catalyst, foam stabilizer, and foaming agent to obtain a compound additive;

[0013] (4) Preparation of aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material: polyisocyanate, precursor solution, aluminum sol / carbon nanotube solution, and compound additives are mixed and foamed, and then cured at high temperature to obtain aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material.

[0014] Furthermore, the aromatic dianhydride in step (1) is one or more of 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride and pyromellitic dianhydride;

[0015] Furthermore, the polar solvent I in step (1) is a mixture of one or more of N,N'-dimethylformamide and N,N'-dimethylacetamide;

[0016] Furthermore, the small molecule alcohol in step (1) is one or more of anhydrous methanol and anhydrous ethanol.

[0017] Furthermore, the carbon nanotubes in step (2) are one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes having an average diameter of 1 to 10 nm and an average length of 1 to 20 μm;

[0018] Furthermore, the polar solvent II in step (2) is a mixture of one or more of dimethyl sulfoxide, N,N'-dimethylformamide, and dichloromethane;

[0019] Furthermore, the aluminum sol in step (2) has a solid content of 20-25% and a pH of 2.0-4.0.

[0020] Furthermore, the flame retardant in step (3) is one or more of expandable graphite modified by doped aluminum sol, graphene oxide, ammonium pentaborate, and phosphorus-containing polyol;

[0021] Furthermore, the catalyst in step (3) is one or more of N,N'-dimethylbutylamine, N,N'-dimethylethanolamine, N-methylmorpholine, N-ethylmorpholine, pyridine, Niax A-1, Niax A-33, trimethyl-N-2-hydroxypropyl hexanoic acid, and dibutyltin dilaurate;

[0022] Furthermore, the foam stabilizer in step (3) is one or more of B-8242, B-8408, DC-2585, DC-5604, L-655, L-5333, AK-8871, H-330, H-360, and Y-10366.

[0023] Furthermore, the foaming agent in step (4) is deionized water and polyethylene glycol;

[0024] Further preferably, the mass ratio of deionized water to polyethylene glycol in the foaming agent is (3-5):4.0.

[0025] Furthermore, the polyisocyanate in step (4) is polymethylene polyphenyl polyisocyanate (PAPI).

[0026] More preferably, the polymethylene polyphenyl polyisocyanate has an isocyanate content of 30.5-32.0%, a viscosity of 150-250 mPa·s at 25° C., and an average functionality of 2.7.

[0027] Furthermore, the stirring and mixing rate in step (1) is 1000-1500 r / min;

[0028] Furthermore, the temperature of the reflux reaction in step (1) is 60-80° C.; the time of the reflux reaction in step (1) is 1.5-2.5 h; and the reflux reaction in step (1) is carried out at a stirring rate of 1000-1500 r / min.

[0029] Furthermore, the ultrasonic dispersion time in step (2) is 15-30 min;

[0030] Furthermore, the ultrasonic mixing time in step (2) is 15-30 minutes;

[0031] Furthermore, the stirring and mixing rate in step (3) is 1000-1500 r / min; and the stirring and mixing time in step (3) is 10-15 min.

[0032] Furthermore, the foaming in step (4) is performed by stirring first and then standing;

[0033] Further preferably, the stirring rate is 800-1000 r / min; the stirring temperature is 25-30° C.; the stirring time is 10-20 s; and the mixture is allowed to stand until the volume remains unchanged.

[0034] Furthermore, the temperature of the high-temperature curing in step (4) is 200-240° C.; and the time of the high-temperature curing in step (4) is 1-3 hours.

[0035] Furthermore, the amount of each raw material used is as follows, calculated by weight:

[0036]

[0037]

[0038] The aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material prepared by the above preparation method.

[0039] This invention uses polyimide foam as a matrix material and employs a solution method to uniformly fill the interior of the polyimide foam with aluminum sol and carbon nanotubes. By optimizing the temperature and dosage parameters during the filling process, the distribution of the aluminum sol and carbon nanotubes within the polyimide foam can be effectively controlled, forming a composite material with a complex pore structure. The resulting aluminum sol / carbon nanotube-filled polyimide foam significantly improves the material's mechanical strength, electrical conductivity, and flame retardancy while maintaining the polyimide foam's lightweight, high porosity, and excellent thermal insulation properties.

[0040] The aluminum particles in the aluminum sol form a dense aluminum oxide layer at high temperatures, further enhancing the material's thermal stability and flame retardancy. The high surface area and unique microstructure of carbon nanotubes further enhance the material's sound absorption properties. Furthermore, the carbonized layer formed by carbon nanotubes at high temperatures effectively slows the material's pyrolysis and reduces the generation of combustible gases, thus broadening the material's application in flame retardancy and sound absorption.

[0041] The flame-retardant polyimide foam sound-absorbing material described in this invention not only exhibits excellent flame retardancy but also demonstrates superior sound absorption. This material is environmentally friendly, economical, practical, and simple to operate, making it suitable for a variety of construction scenarios, particularly for use on building exterior and interior walls. Potential applications include exterior walls of buildings such as urban residential communities and hotels, concrete surfaces on highways and high-speed railways, and tunnel interiors. It can effectively enhance the sound absorption and fire resistance of buildings in complex environments, providing an ideal solution for reducing environmental noise and improving safety.

[0042] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0043] (1) In the method for preparing the aluminum sol / carbon nanotube composite polyimide foam provided by the present invention, the aluminum sol / carbon nanotubes are uniformly dispersed in the polyimide precursor solution using a solution mixing method. Compared with the traditional direct filling method, this method ensures a more uniform distribution of the aluminum sol / carbon nanotubes in the polyimide foam, effectively avoiding pore clogging caused by carbon nanotube aggregation, while also improving the overall performance of the material.

[0044] (2) The composite filling of carbon nanotubes and aluminum sol in the present invention not only optimizes the pore structure of the polyimide foam and enhances the mechanical properties of the material, but also significantly improves the sound absorption effect of the foam material by increasing the viscous damping at the interface. Especially in high temperature environments, the presence of aluminum sol further enhances the flame retardant properties of the material, making it have more excellent acoustic and fire resistance.

[0045] (3) The sound-absorbing material prepared by the present invention is environmentally friendly and non-toxic, and exhibits good storage stability. It can be stored in cans for long periods of time, reducing the time and labor costs for mixing ingredients at the construction site and improving construction efficiency. The addition of aluminum sol has no negative impact on the environmental friendliness of the material, but rather enhances its wide application.

[0046] (4) The polyimide foam sound-absorbing material prepared by the present invention is lightweight, easy to process, and convenient to install. It can be cut into different sizes and shapes according to actual needs and is suitable for sound absorption treatment of various building structures. This material can be widely used in various scenarios such as residential areas, hotels, sound barriers on highways and high-speed railways, and tunnel interior walls, effectively improving the sound absorption performance and safety of buildings. In particular, high-frequency noise (2kHz-8kHz) to which the human ear is sensitive requires special control. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1a and Figure 1b Scanning electron microscope images of the flame-retardant polyimide foam sound-absorbing material prepared in Example 1 at different magnifications;

[0048] Figure 1c and Figure 1d Scanning electron microscope images of the flame-retardant polyimide foam sound-absorbing material prepared in Example 2 at different magnifications;

[0049] Figure 1e and Figure 1f Scanning electron microscope images of the flame-retardant polyimide foam sound-absorbing material prepared in Example 3 at different magnifications;

[0050] Figure 2 This is the thermal stability curve of the flame-retardant polyimide foam sound-absorbing material prepared in Examples 1 to 3;

[0051] Figure 3 The limiting oxygen index of the flame retardant polyimide foam sound absorbing materials prepared in Examples 1 to 3 and Comparative Examples 1 and 2;

[0052] Figure 4 The sound absorption coefficients of the flame-retardant polyimide foam sound-absorbing materials prepared in Examples 1 to 3 and Comparative Examples 1 and 2 are shown. DETAILED DESCRIPTION

[0053] The present invention is further described in detail below with reference to the accompanying drawings and specific examples. The examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials and reagents used are commercially available unless otherwise specified.

[0054] In the following examples and comparative examples, parts are expressed by weight (mass). Weight units may be grams, kilograms, or any other commonly used amount in the art. The aluminum sol used had a solids content of 2.3% and a pH of 3.0. The PAPI used had an isocyanate content of 30.5-32.0%, a viscosity of 150-250 mPa·s at 25°C, and an average functionality of 2.7.

[0055] Example 1

[0056] (1) Preparation of precursor solution:

[0057] 100 parts of 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 100 parts of N,N'-dimethylformamide, and 30 parts of anhydrous methanol were added to a three-necked flask. The rotor stirring rate was set to 1200 r / min, and the system was refluxed at a constant temperature of 75°C for 1.5 hours to obtain a light yellow clear precursor solution.

[0058] (2) Preparation of aluminum sol modified carbon nanotubes:

[0059] Take 0.1 parts of single-walled carbon nanotubes with an average diameter of 1 nm and an average length of 1.5 μm and 50 parts of dimethyl sulfoxide, mix them, and ultrasonicate them for 15 minutes to make them evenly dispersed. Then add 1.0 parts of aluminum sol and continue ultrasonicating for 15 minutes to obtain an aluminum sol / carbon nanotube mixed solution.

[0060] (3) Preparation of compound additives:

[0061] Take 15 parts of flame retardant (expandable graphite modified by doping with aluminum sol), 1.6 parts of catalyst (0.3 parts of trimethyl-N-2-hydroxypropyl hexanoic acid, 0.3 parts of dibutyltin dilaurate, 1.0 parts of N,N'-dimethylbutylamine), 3.5 parts of foam stabilizer (DC-2585), 7.75 parts of foaming agent (3.75 parts of deionized water, 4.0 parts of polyethylene glycol), stir thoroughly at a stirring rate of 1500 r / min and a stirring time of 10 min to obtain a compound additive.

[0062] (4) Preparation of aluminum sol / carbon nanotube composite flame retardant polyimide foam sound absorbing material:

[0063] Take 25 parts of PAPI, then add the precursor solution described in step (1), the mixed solution described in step (2) and the compound additive described in step (3), stir thoroughly at 25°C, and the stirring rate is 1000r / min. After stirring for 10s, pour it into a specific opening mold quickly, let it stand, and after the foaming height remains unchanged, high temperature cure at 210°C for 1.5h to obtain an aluminum sol / carbon nanotube composite flame retardant polyimide foam sound absorbing material.

[0064] The morphology of the flame retardant polyimide foam sound absorbing material prepared in Example 1 is shown in FIG. Figure 1a and Figure 1b shown.

[0065] The flame retardant polyimide foam sound absorbing material was characterized by thermal stability, limiting oxygen index and sound absorption coefficient. The results are shown in Figure 2 、 Figure 3 and Figure 4 shown.

[0066] from Figure 1a and Figure 1b It can be seen that at low magnification, the pores present a uniform open-pore structure with relatively consistent pore size; at high magnification, the aluminum sol / carbon nanotubes are evenly distributed and tightly attached to the pore walls of the foam.

[0067] in addition, Figure 2 Thermogravimetric curve, from Figure 2 It can be seen that the residual weight rate of the flame-retardant polyimide foam sound-absorbing material prepared in Example 1 is about 47%.

[0068] The flame retardant polyimide foam sound absorbing material prepared in Example 1 was tested according to GB / T 2406.2-2009 Plastics Oxygen Index Method for Determination of Combustion Behavior Part 2: Room Temperature Test. The test results are as follows: Figure 3 .from Figure 3 It can be seen that the flame retardant material described in Example 1 exhibits good flame retardant properties, with a limiting oxygen index as high as 31.5%.

[0069] The flame retardant polyimide foam sound absorbing material prepared in Example 1 was tested according to GB / T 18696.1-2004 Measurement of sound absorption coefficient and acoustic impedance in acoustic impedance tubes Part 1: Standing wave ratio method. The test results are as follows: Figure 4 .from Figure 4 It can be seen that the sound absorbing material described in Example 1 exhibits good sound absorption performance, with an average sound absorption coefficient as high as 0.73.

[0070] Example 2

[0071] (1) Preparation of precursor solution:

[0072] 85 parts of pyromellitic dianhydride, 90 parts of N,N'-dimethylacetamide, and 25 parts of anhydrous ethanol were added to a three-necked flask, the rotor stirring rate was set to 1500 r / min, and the system was refluxed at a constant temperature of 70°C for 2 hours to obtain a light yellow clear precursor solution.

[0073] (2) Preparation of aluminum sol modified carbon nanotubes:

[0074] Take 0.5 parts of multi-walled carbon nanotubes with an average diameter of 1 nm and an average length of 5 μm and 60 parts of dimethyl sulfoxide, mix them, and ultrasonicate for 20 minutes to make them evenly dispersed. Then add 2.0 parts of aluminum sol and continue ultrasonicating for 20 minutes to obtain an aluminum sol / carbon nanotube mixed solution.

[0075] (3) Preparation of compound additives:

[0076] Take 18 parts of flame retardant (ammonium pentaborate), 2.4 parts of catalyst (0.6 parts of trimethyl-N-2-hydroxypropyl hexanoic acid, 0.4 parts of dibutyltin dilaurate, 1.4 parts of N,N'-dimethylbutylamine), 1.5 parts of foam stabilizer (L-655), 5.25 parts of foaming agent (2.75 parts of deionized water, 2.5 parts of polyethylene glycol), stir thoroughly at a stirring rate of 1500 r / min and a stirring time of 12 min to obtain a compound additive.

[0077] (4) Preparation of aluminum sol / carbon nanotube composite flame retardant polyimide foam sound absorbing material:

[0078] Take 25 parts of PAPI, then add the precursor solution described in step (1), the mixed solution described in step (2) and the compound additive described in step (3), stir thoroughly at 27°C, with a stirring rate of 1000r / min, stir for 15s, quickly pour into a specific opening mold, let it stand, and after the foaming height remains unchanged, high-temperature cure at 220°C for 2h to obtain an aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material.

[0079] The morphology of the flame retardant polyimide foam sound absorbing material prepared in Example 2 is shown in FIG. Figure 1c and Figure 1d shown.

[0080] The flame retardant polyimide foam sound absorbing material was characterized by thermal stability, limiting oxygen index and sound absorption coefficient. The results are shown in Figure 2 、 Figure 3 and Figure 4 shown.

[0081] from Figure 1c and Figure 1d It can be seen that under low magnification, the pore structure presents a consistent open pore morphology and a uniform pore size distribution; under high magnification, the aluminum sol / carbon nanotubes are evenly covered on the pore wall of the foam and are tightly combined.

[0082] in addition, Figure 2 Thermogravimetric curve, from Figure 2 It can be seen that the residual weight rate of the flame-retardant polyimide foam sound-absorbing material prepared in Example 2 is about 48%, which is close to the residual weight rate of Example 1.

[0083] The flame retardant polyimide foam sound absorbing material prepared in Example 2 was tested according to GB / T 2406.2-2009 Plastics Oxygen Index Method for Determination of Combustion Behavior Part 2: Room Temperature Test. The test results are as follows: Figure 3 .from

[0084] Figure 3 It can be seen that the flame retardant material described in Example 2 exhibits good flame retardant properties, with a limiting oxygen index as high as 35.2%.

[0085] The flame retardant polyimide foam sound absorbing material prepared in Example 2 was tested for sound absorption performance according to the national standard GB / T18696.1-

[0067] 2004 "Measurement of sound absorption coefficient and acoustic impedance in acoustic impedance tubes" Part 1: Standing wave ratio method. The test results are as follows: Figure 4 .from Figure 4 It can be seen that the sound absorbing material described in Example 2 exhibits good sound absorption performance, with an average sound absorption coefficient as high as 0.78.

[0086] Example 3

[0087] (1) Preparation of precursor solution:

[0088] Take 70 parts of 3,3',4,4'-biphenyltetracarboxylic dianhydride, 80 parts of N,N'-dimethylacetamide, 10 parts of anhydrous methanol, and 10 parts of anhydrous ethanol and add them into a three-necked flask. The rotor stirring rate is set to 1300 r / min. The system is refluxed at a constant temperature of 65°C for 2.5 hours to obtain a light yellow clear precursor solution.

[0089] (2) Preparation of aluminum sol modified carbon nanotubes:

[0090] Take 1.0 parts of multi-walled carbon nanotubes with an average diameter of 5 nm and an average length of 15 μm and 70 parts of dimethyl sulfoxide, mix them, and ultrasonicate them for 20 minutes to make them evenly dispersed. Then add 2.5 parts of aluminum sol and continue ultrasonicating for 20 minutes to obtain an aluminum sol / carbon nanotube mixed solution.

[0091] (3) Preparation of compound additives:

[0092] Take 15 parts of flame retardant (phosphorus-containing polyol), 1.9 parts of catalyst (0.6 parts of trimethyl-N-2-hydroxypropyl hexanoic acid, 0.3 parts of dibutyltin dilaurate, 1.0 parts of N,N'-dimethylbutylamine), 2.5 parts of foam stabilizer (AK-8871), 6.75 parts of foaming agent (3.25 parts of deionized water, 3.5 parts of polyethylene glycol), stir thoroughly at a stirring rate of 1400 r / min and a stirring time of 15 min to obtain a compound additive.

[0093] (4) Preparation of aluminum sol / carbon nanotube composite flame retardant polyimide foam sound absorbing material:

[0094] Take 25 parts of PAPI, add the mixed solution described in step (2) and the compound additive described in step (3), stir thoroughly at 25°C, and stir at a rate of 1000 r / min. After stirring for 20 seconds, pour it into a specific opening mold quickly, let it stand, and after the foaming height remains unchanged, high-temperature cure it at 210°C for 2.5 hours to obtain an aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material.

[0095] The morphology of the flame retardant polyimide foam sound absorbing material prepared in Example 3 is shown in FIG. Figure 1e and Figure 1f shown.

[0096] The flame retardant polyimide foam sound absorbing material was characterized by thermal stability, limiting oxygen index and sound absorption coefficient. The results are shown in Figure 2 、 Figure 3 and Figure 4 shown.

[0097] from Figure 1e and Figure 1f It can be seen from the figure that under low magnification, the pore structure still presents a consistent open pore morphology and a uniform pore size distribution; under high magnification, the distribution density of the aluminum sol / carbon nanotubes is significantly higher than that of the carbon nanotubes in Example 2.

[0098] in addition, Figure 2 Thermogravimetric curve, from Figure 2 It can be seen that the residual weight rate of the flame retardant polyimide foam sound-absorbing material prepared in Example 3 is 36%.

[0099] The flame retardant polyimide foam sound absorbing material prepared in Example 3 was tested according to GB / T 2406.2-2009 Plastics Oxygen Index Method for Determination of Combustion Behavior Part 2: Room Temperature Test. The test results are as follows: Figure 3 .from Figure 3 It can be seen that the flame retardant material described in Example 3 exhibits good flame retardant properties, with a limiting oxygen index as high as 38.6%.

[0100] The flame retardant polyimide foam sound absorbing material prepared in Example 3 was tested for sound absorption performance according to the national standard GB / T18696.1-

[0067] 2004 "Measurement of sound absorption coefficient and acoustic impedance in acoustic impedance tubes" Part 1: Standing wave ratio method. The test results are as follows: Figure 4 .from Figure 4 It can be seen that the sound absorbing material described in Example 3 exhibits good sound absorption performance, with an average sound absorption coefficient as high as 0.83.

[0101] Combining Examples 1, 2, and 3 and their variations in sound absorption coefficient at low frequencies (0-500 Hz), mid-frequency frequencies (500-2000 Hz), and high frequencies (2000-5000 Hz), it can be concluded that while the sound absorption coefficient is generally low (approximately 0.2-0.6) in the 0-500 Hz range, Example 3's sound absorption coefficient is significantly higher than the other examples, approaching 0.5-0.6 and rising rapidly. Example 1 exhibits the weakest sound absorption performance. From 500-2000 Hz, Example 3 exhibits the highest sound absorption coefficient (0.8-0.9) with minimal fluctuation, demonstrating stable sound absorption performance. Example 2 follows closely behind, with a sound absorption coefficient of 0.7-0.85. Example 1 exhibits the lowest sound absorption coefficient (0.6-0.8) with significant fluctuations. From 2000-5000 Hz, the sound absorption performance of the examples tends to be stable, with Example 3 exhibiting a sound absorption coefficient approaching 0.9, the best performance of all samples. With the addition of aluminum sol / carbon nanotubes, the embodiment has limited performance improvement in the low-frequency band, but shows excellent control ability for mid- and high-frequency noise, which is particularly suitable for application scenarios such as conference rooms, theaters or high-frequency equipment noise reduction.

[0102] Comparative Example 1

[0103] Comparative Example 1 was carried out with reference to Example 1, but without the step (2) in Example 1, and the aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material described in step (4) was replaced with a flame-retardant polyimide foam sound-absorbing material not doped with aluminum sol / carbon nanotubes.

[0104] The flame retardant polyimide foam sound absorbing material without aluminum sol / carbon nanotubes prepared in Comparative Example 1 was tested for limiting oxygen index and sound absorption performance, respectively. Figure 3 、 4 .

[0105] The flame retardant performance of the flame retardant polyimide foam sound absorbing material without aluminum sol / carbon nanotubes prepared in Comparative Example 1 was tested. The test results are as follows: Figure 3 .from Figure 3 It can be seen that the limiting oxygen index of the flame retardant material described in Comparative Example 1 is only 22.1%. By comparing the examples with the comparative examples, it is found that the introduction of aluminum sol / carbon nanotubes can effectively improve the flame retardant performance. Compared with Comparative Example 1, the limiting oxygen index of Example 1 is increased by 42.5%.

[0106] The flame retardant polyimide foam sound absorbing material prepared in Comparative Example 1 without adding carbon nanotubes was tested for sound absorption performance. The test results are as follows: Figure 4 .from Figure 4 It can be seen that the average sound absorption coefficient of the sound absorbing material described in Comparative Example 1 is only 0.53.

[0107] Comparative Example 2

[0108] Comparative Example 2 was carried out with reference to Example 1, omitting the operation of adding aluminum sol in step (2) and replacing the aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material in step (4) with a flame-retardant polyimide foam sound-absorbing material to which only carbon nanotubes were added.

[0109] The flame retardant polyimide foam sound absorbing material prepared in Comparative Example 2 with only carbon nanotubes added was subjected to limiting oxygen index and sound absorption performance tests, respectively. Figure 3 、 4 .

[0110] The flame retardant polyimide foam sound absorbing material prepared in Comparative Example 2 with only carbon nanotubes added was tested for flame retardancy. The test results are as follows: Figure 3 .from Figure 3 It can be seen that the limiting oxygen index of the flame retardant material described in Comparative Example 2 is only 25.3%. By comparing with the embodiment and Comparative Example 1, it is found that adding only carbon nanotubes can improve the flame retardancy, but the flame retardancy effect is not as significant as adding aluminum sol / carbon nanotubes.

[0111] The flame retardant polyimide foam sound absorbing material prepared in Comparative Example 2 with only carbon nanotubes added was tested for sound absorption performance. The test results are as follows: Figure 4 .from Figure 4 It can be seen that the average sound absorption coefficient of the sound absorbing material described in Comparative Example 2 is 0.64.

[0112] Combining 3 embodiments and 2 comparative examples,

[0113] Comparative analysis of their flame retardant properties shows that:

[0114] ① Flame retardancy improved gradually from Example 1 to Example 3, with LOI increasing from 31.5% to 38.6%. Example 3 introduced higher-density carbon nanotubes and aluminum sol. These materials formed a denser protective layer (carbonized layer) during combustion, effectively preventing oxygen from entering, thereby improving flame retardancy.

[0115] ② Comparative Example 1 has the lowest limiting oxygen index. Aluminum sol and carbon nanotubes are not added. An effective carbonization layer and heat barrier cannot be formed during combustion, resulting in rapid diffusion of oxygen and accelerated combustion.

[0116] ③ The LOI of Comparative Example 2 was 25.3%, slightly higher than that of Comparative Example 1, an improvement of only 14%, but still significantly lower than that of the Examples. Carbon nanotubes promote the formation of a carbonized layer during combustion, but lack the synergistic effect of alumina sol, preventing them from forming an additional ceramic protective layer at high temperatures. While carbon nanotubes contribute to flame retardancy, their effect alone is limited and requires combination with alumina sol for optimal flame retardancy.

[0117] Therefore, the synergistic effect of aluminum sol and carbon nanotubes is the core of improving flame retardant properties. The combination of the two can significantly enhance the density and protective effect of the carbonized layer.

[0118] Comparative analysis of the sound absorption performance of different sound frequency bands shows that:

[0119] ① Comparative Examples 1 and 2 have similar sound absorption performance in the low-frequency range, with sound absorption coefficients of approximately 0.2-0.3, respectively, which is significantly lower than that of the embodiment. Comparative Example 2 is slightly better than Comparative Example 1, but neither can effectively absorb low-frequency sound waves in the low-frequency range.

[0120] ② The gap in sound absorption performance between Comparative Example 1 and Comparative Example 2 in the mid-frequency band is significantly widened: the sound absorption coefficient of Comparative Example 2 is between 0.5-0.65, slightly higher than that of Comparative Example 1. The sound absorption coefficient of Comparative Example 1 is 0.4-0.6, and the sound absorption effect is poor. Only adding carbon nanotubes (Comparative Example 2) improves the sound wave absorption capacity of the pore wall in the mid-frequency band, but without the further enhancement of aluminum sol, its effect is limited. Carbon nanotubes play a certain role in the mid-frequency band, but they need to be combined with other reinforcing materials (such as aluminum sol) to significantly improve the overall sound absorption performance.

[0121] ③ The difference in sound absorption performance between Comparative Examples 1 and 2 at 2000-5000 Hz gradually decreases: the sound absorption coefficient of Comparative Example 2 is approximately 0.65, slightly higher than the 0.6 of Comparative Example 1. There is still a significant difference between these two and the Example, indicating that the addition of carbon nanotubes alone is not sufficient to significantly improve high-frequency sound absorption performance. High-frequency sound waves have shorter wavelengths and are more dependent on the uniformity of the pore wall distribution and the sound wave scattering ability of the pore wall surface. The introduction of aluminum sol makes the pore wall denser and enhances sound absorption performance.

[0122] In summary, the present invention addresses the current shortage of sound-absorbing materials that are widely applicable, low in cost, environmentally friendly, and have excellent sound absorption and flame retardant effects. A method for preparing an aluminum sol / carbon nanotube flame-retardant polyimide foam sound-absorbing material with both high flame retardant and sound absorption properties is proposed.

[0123] The above embodiments and comparative examples are merely preferred embodiments of the present invention and are only used to explain the present invention rather than to limit the present invention. Any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of protection of the present invention.

Claims

1. A method for preparing an aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material, characterized in that: The steps include: (1) Preparation of a precursor solution: Aromatic dianhydride, polar solvent I, and small molecule alcohol are stirred and mixed, and refluxed to obtain a precursor solution; (2) Preparation of aluminum sol-modified carbon nanotubes: dispersing carbon nanotubes in polar solvent II, ultrasonically dispersing, adding aluminum sol, and continuing ultrasonic mixing to obtain an aluminum sol / carbon nanotube solution; (3) Preparation of compound additives: mixing the flame retardant, the catalyst, the foam stabilizer and the foaming agent to obtain a compound additive; (4) Preparation of aluminum sol / carbon nanotube composite flame retardant polyimide foam sound absorbing material: polyisocyanate, precursor solution, aluminum sol / carbon nanotube solution, and compound additives are mixed and foamed, and then cured at high temperature to obtain aluminum sol / carbon nanotube composite flame retardant polyimide foam sound absorbing material.

2. The method for preparing the aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material according to claim 1, characterized in that: The aromatic dianhydride in step (1) is one or more of 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,4,5,8-naphthalenetetracarboxylic dianhydride and pyromellitic dianhydride; the polar solvent I in step (1) is a mixture of one or more of N,N'-dimethylformamide and N,N'-dimethylacetamide; the small molecule alcohol in step (1) is one or more of anhydrous methanol and anhydrous ethanol.

3. The method for preparing the aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material according to claim 1, characterized in that: The carbon nanotubes in step (2) are one or more of single-walled carbon nanotubes and multi-walled carbon nanotubes with an average diameter of 1 to 10 nm and an average length of 1 to 20 μm; the polar solvent II in step (2) is a mixture of one or more of dimethyl sulfoxide, N,N'-dimethylformamide, and dichloromethane; the solid content of the aluminum sol in step (2) is 20-25%, and the pH is 2.0-4.

0.

4. The method for preparing the aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material according to claim 1, characterized in that: The flame retardant in step (3) is one or more of expandable graphite modified by doping aluminum sol, graphene oxide, ammonium pentaborate, and phosphorus-containing polyol; The catalyst in step (3) is one or more of N,N'-dimethylbutylamine, N,N'-dimethylethanolamine, N-methylmorpholine, N-ethylmorpholine, pyridine, Niax A-1, Niax A-33, trimethyl-N-2-hydroxypropylhexanoic acid, and dibutyltin dilaurate; The foam stabilizer in step (3) is one or more of B-8242, B-8408, DC-2585, DC-5604, L-655, L-5333, AK-8871, H-330, H-360, and Y-10366.

5. The method for preparing the aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material according to claim 1, characterized in that: The foaming agent in step (4) is deionized water and polyethylene glycol; The polyisocyanate in step (4) is polymethylene polyphenyl polyisocyanate.

6. The method for preparing the aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material according to claim 1, characterized in that: The stirring and mixing rate in step (1) is 1000-1500 r / min; The temperature of the reflux reaction in step (1) is 60-80° C.; the time of the reflux reaction in step (1) is 1.5-2.5 h; and the reflux reaction in step (1) is carried out at a stirring rate of 1000-1500 r / min.

7. The method for preparing the aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material according to claim 1, characterized in that: The ultrasonic dispersion time in step (2) is 15-30 min; The ultrasonic mixing time in step (2) is 15-30 minutes; The stirring and mixing rate in step (3) is 1000-1500 r / min; the stirring and mixing time in step (3) is 10-15 min.

8. The method for preparing the aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material according to claim 1, characterized in that: The foaming in step (4) is performed by stirring first and then standing; the stirring rate is 800-1000 r / min; the stirring temperature is 25-30° C.; the stirring time is 10-20 s; and the foam is left standing until the volume remains unchanged; The temperature of the high temperature curing in step (4) is 200-240° C.; the time of the high temperature curing in step (4) is 1-3 hours.

9. The method for preparing the aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material according to claim 1, characterized in that: According to the mass fraction, Aromatic dianhydride 80-110 parts; Polar solvent I 70-110 parts; 20-35 parts of small molecule alcohol; 0.1-1.0 parts of carbon nanotubes; Polar solvent II 5-50 parts; Aluminum sol 0.5-10 parts; Flame retardant 10-35 parts; 1-5 parts of catalyst; Foam stabilizer 1-4 parts; 5-8 parts of foaming agent; Polyisocyanate 20-30 parts.

10. Aluminum sol / carbon nanotube composite flame-retardant polyimide foam sound-absorbing material prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Polyimide foam sound absorption material with high aperture ratio and preparation method thereof

    CN114773656A

  • Polyimide foam material for sound absorption and preparation method thereof

    CN115011121A

  • Sound-absorbing material, sound-generating device, and electronic apparatus

    CN116709136A

  • Porous composite material for sound absorption and method of producing same

    US20220243022A1